Influence of masks on speech perception in people with cochlear implants - Teira, Celia; Pomares Gómez, Irene (Revista de Investigación en Logopedia, 2022)
The use of face masks in the COVID-19 health crisis is rising many questions, one of them being the effect that they potentially have in language perception in deaf people who use a cochlear implant. To shed some light, an experimental study has been made on the discrimination of minimal pairs in Spanish. In this experiment, we studied the presence or absence of face mask, as well the possibility to read lip and facial expressions. Results support face masks interfere in perception, especially in people with cochlear implant, but multimodality does not improve it as we expected.